1992
DOI: 10.1111/j.1365-2265.1992.tb02354.x
|View full text |Cite
|
Sign up to set email alerts
|

Body composition and bone mass in post‐menopausal women

Abstract: Both fat and lean tissue mass are related to total and regional bone mass in post-menopausal women, the relationship being strongest for fat mass. Body weight shows stronger correlations with bone mass than either height or body mass index. In view of the direction and magnitude of changes in fat, lean tissue and bone mineral after the menopause, adiposity and muscularity are more likely to be determinants of peak bone mass than of the rate of post-menopausal bone loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(64 citation statements)
references
References 26 publications
5
57
0
2
Order By: Relevance
“…The results of Hla et al 57 agree with those of Compston et al, 58 Sowers et al 59 and Edelstein and Barrett-Connor. 60 Reid et al 61 thought fat mass more important than lean and neither oestrone production or physical loading could explain the effect while Sowers et al 59 concluded that higher fat mass is only protective with higher lean mass.…”
Section: Bone Healthsupporting
confidence: 65%
“…The results of Hla et al 57 agree with those of Compston et al, 58 Sowers et al 59 and Edelstein and Barrett-Connor. 60 Reid et al 61 thought fat mass more important than lean and neither oestrone production or physical loading could explain the effect while Sowers et al 59 concluded that higher fat mass is only protective with higher lean mass.…”
Section: Bone Healthsupporting
confidence: 65%
“…The pattern of the association between TRUNK FM and total body BMC was similar. The only significant association 6 between TRUNK FM / LEG FM ratio and BMCTOT was in men < 50 (R 2 =0.124). There was a significant association between TOT LM and BMCTOT in both men and women in the two age groups.…”
Section: Resultsmentioning
confidence: 94%
“…In men, lean mass seems to be strongly related to BMD [1][2][3]. In women, some cross-sectional studies in pre-and postmenopausal subjects [2,4,5] suggest that BMD is related to fat mass while in other studies [1,[6][7][8], both lean and fat mass were related to bone mass. More studies have been conducted on women and only a few studies have directly compared gender differences in the relationship between body composition and BMD [3,9].…”
Section: Introductionmentioning
confidence: 99%
“…An ample amount of work has been done to investigate the intra-and inter-site precision of DXA for bone (Mazess et al, 1990;Johnson et al, 1991;LeBlanc et al, 1990;Mazess et al, 1989;Nuti et al, 1987;Compston et al, 1992;Kelly et al, 1991;Economos et al, 1996;Seto et al, 1991). Within the last ®ve years, quite a few studies examining soft tissue intra-site precision have been published (see Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The precision of individual DXA instruments for the assessment of bone is excellent, with coef®cients of variation (CV)`1.0% (Johnson et al, 1991;LeBlanc et al, 1990;Mazess et al, 1989;Nuti et al, 1987;Compston et al, 1992). On the other hand, Cvs for soft tissue measurements of up to 3.1% for lean tissue, 8.6% for fat tissue, and 7.9% for percent body fat have been observed (Table 1) Mazess et al, 1990;Johnson et al, 1991;Compston et al, 1992;Kelly et al, 1991;Slosman et al, 1992;Haarbo et al, 1991;Pritchard et al, 1993;Rico et al, 1994). The difference in precision between bone and soft tissue is not surprising since DXA was essentially designed to assess bone and soft tissue is heterogeneous.…”
Section: Introductionmentioning
confidence: 99%